2016
DOI: 10.1099/ijsem.0.001145
|View full text |Cite
|
Sign up to set email alerts
|

Actinorhabdospora filicis gen. nov., sp. nov., a new member of the family Micromonosporaceae

Abstract: The actinomycete strains K12-0408 T and K12-0792 were isolated on CM-cellulose agar from rhizosphere soil of a pteridophytic plant collected in Tokyo prefecture, Japan. Their taxonomic positions were determined using a polyphasic approach. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strains K12-0408 T and K12-0792 were positioned within the family Micromonosporaceae. The strains formed extensively branched aerial and substrate mycelia. Long chains of cylindrical spores with smooth surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This study was designed to explore the extent to which whole genome sequence data derived from type strains of the genus Micromonospora can be used to clarify relationships within this taxon and provide insights into the biological properties and biotechnological potential of micromonosporae. The genus Micromonospora 44 is the type genus of the family Micromonosporaceae 45 of the order Micromonosporales 46 ; the family encompasses 31 validly named genera which can be distinguished using a combination of chemotaxonomic, morphological and phylogenetic criteria 45 , 47 . The genus was proposed by Ørskov in 1923 48 for strains isolated from air that had been designated as “ Streptothrix chalcea ” by Foulerton 49 and then reclassified as Micromonospora chalcea , the type species of the genus.…”
Section: Introductionmentioning
confidence: 99%
“…This study was designed to explore the extent to which whole genome sequence data derived from type strains of the genus Micromonospora can be used to clarify relationships within this taxon and provide insights into the biological properties and biotechnological potential of micromonosporae. The genus Micromonospora 44 is the type genus of the family Micromonosporaceae 45 of the order Micromonosporales 46 ; the family encompasses 31 validly named genera which can be distinguished using a combination of chemotaxonomic, morphological and phylogenetic criteria 45 , 47 . The genus was proposed by Ørskov in 1923 48 for strains isolated from air that had been designated as “ Streptothrix chalcea ” by Foulerton 49 and then reclassified as Micromonospora chalcea , the type species of the genus.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study that observed a positive correlation of soil potassium and the genera Oikopleura , Actinorhabdospora , Enteractinococcus , Paenisporosarcina , Thiobacillus , Ornithinicoccus , Oleiagrimonas , Candidatus Caldatribacterium , Anseongella , Bhargavaea , Globicatella , Planococcus , OLB17 , Xenophilus and Mitsuaria . These groups of bacteria were largely found in soils of cultures other than grapevines, although no correlation analysis with nutrients have been previously shown [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ]. Dietzia and Xenophilus have also been found in other studies on grapevine soil [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%